Estimating Zero Waste Index and Resident Waste Participation in Indonesian Middle City - Muhammad Nizar; Rahadian Zainul; Syaifuddin Yana; Erdiwansyah Erdiwansyah; Irda Yunita (Jurnal Serambi Engineering, 2022)
The municipal city has tried to provide the best solid waste services as possible, but the increase in these services does not necessarily increase public participation in managing waste. The objective of this research is to measure the performance of municipal solid waste management while Banda Aceh Indonesia. The research method uses the Zero Waste Index tool and community surveyed to get a more comprehensive picture of performance in overcoming waste problems. The results can be concluded that the Banda Aceh city government is still achieving a small Zero Waste Index which is 0.28. The majority of the population does not get waste socialization (76.07%), does not sort (75.21%), does not recycle waste (68.31%) and only 54.70% of the community collect used items for resale. The results of the two studies show that it is hard for Banda Aceh to achieve the goal of 30% waste reduction by 2025.